<span>A)x-y+3 is your answer
Proof:
(5 x)/4 - 8 y - x/4 + 7 y + 3
Put each term in (5 x)/4 - 8 y - x/4 + 7 y + 3 over the common denominator 4: (5 x)/4 - 8 y - x/4 + 7 y + 3 = (5 x)/4 - (32 y)/4 - (x)/4 + (28 y)/4 + 12/4:
(5 x)/4 - (32 y)/4 - x/4 + (28 y)/4 + 12/4
(5 x)/4 - (32 y)/4 - x/4 + (28 y)/4 + 12/4 = (5 x - 32 y - x + 28 y + 12)/4:
(5 x - 32 y - x + 28 y + 12)/4
Grouping like terms, 5 x - 32 y - x + 28 y + 12 = (28 y - 32 y) + (5 x - x) + 12:
((28 y - 32 y) + (5 x - x) + 12)/4
28 y - 32 y = -4 y:
(-4 y + (5 x - x) + 12)/4
5 x - x = 4 x:
(-4 y + 4 x + 12)/4
Factor 4 out of -4 y + 4 x + 12:
(4 (-y + x + 3))/4
(4 (-y + x + 3))/4 = 4/4×(3 + x - y) = 3 + x - y:
Answer: 3 + x - y
</span>
1/2x + 3 = 2/3x + 1....multiply everything by the common denominator of 6
3x + 18 = 4x + 6
3x - 4x = 6 - 18
-x = - 12
x = 12 <====
multiplying by the common denominator will get rid of the fractions
Answer:
-7/3
Step-by-step explanation:
2(6−4)=3(6+2)
2(6x-4)=3(6x+2)
Solve
1
Distribute
2(6−4)=3(6+2)
{\color{#c92786}{2(6x-4)}}=3(6x+2)
12−8=3(6+2)
{\color{#c92786}{12x-8}}=3(6x+2)
2
Distribute
12−8=3(6+2)
12x-8={\color{#c92786}{3(6x+2)}}
12−8=18+6
12x-8={\color{#c92786}{18x+6}}
3
Add
8
8
to both sides of the equation
12−8=18+6
12x-8=18x+6
12−8+8=18+6+8
12x-8+{\color{#c92786}{8}}=18x+6+{\color{#c92786}{8}}
5 more steps
Solution
=−7/3
I have no idea what this means im in 6th grade
Answer:
1. (0,0) (3,1) (6,2)
2. proportinal
3. im so sorry but i cant see that one i really am sorry!
Step-by-step explanation:
i hope i helped brainliest?